2015
DOI: 10.1136/thoraxjnl-2014-206461
|View full text |Cite
|
Sign up to set email alerts
|

Lactate on emergency department arrival as a predictor of mortality and site-of-care in pneumonia patients: a cohort study

Abstract: Lactate is superior to CURB-65 in predicting mortality, hospitalisation and ICU admission in pneumonia patients in the ED. LAC-CURB-65 significantly improved the predictive value of CURB-65.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 24 publications
6
57
1
1
Order By: Relevance
“…The PSI assigns 30 additional points to patients with neoplastic disease, and therefore cancer patients are given higher points. Chen et al 24 studied patients with unselected pneumonia, CAP or HCAP, and found that elevated lactate levels on ED arrival was associated with increased mortality in these cases. In our current study series, most patients (81%) were categorized as high risk using the PSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSI assigns 30 additional points to patients with neoplastic disease, and therefore cancer patients are given higher points. Chen et al 24 studied patients with unselected pneumonia, CAP or HCAP, and found that elevated lactate levels on ED arrival was associated with increased mortality in these cases. In our current study series, most patients (81%) were categorized as high risk using the PSI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Shapiro et al 22 demonstrated that a single measurement of venous lactate provides risk-stratification information about inhospital mortality within 3 days. Chen et al 24 studied patients with unselected pneumonia, CAP or HCAP, and found that elevated lactate levels on ED arrival was associated with increased mortality in these cases. They also showed that lactate levels alone performed better in predicting mortality than CURB-65.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective observational study comparing CURB-65 and serum lactate in 1641 patient with CAP showed that lactate better predicted 28-day mortality, hospitalization, and ICU admission. 33 Lactate should routinely be drawn along with blood cultures as part of the workup for patients being hospitalized with severe CAP to help guide resuscitation, treatment, and disposition.…”
Section: Diagnosis: Additional Testingmentioning
confidence: 99%
“…A more familiar metabolomic example, which has been used in critical care for prognosis and severity, is lactate. In adults with pneumonia, the lactate level has been shown to be a better predictor of 28-day mortality than the CURB-65 score, and a combination of CURB-65 with lactate level improves the predictive value of CURB-65 score alone [35]. For further reading Nickler and colleagues have written an interesting review article looking at this growing field and its impact on our understanding of respiratory conditions [32].…”
Section: The Futurementioning
confidence: 99%